The Violence of Women Depicted in The Breadwinner Novel by Deborah Ellis - Rosmiati (Prologue: Journal on Language and Literature, 2023)
This research intends to explores the cause of women violence in the Taliban’s women. There are two objectives of this research; 1) to find the forms of violence system embraced by the Taliban portrayed in The Breadwinner novel and 2) to describe how Taliban’s affect women powerlessness in The Breadwinner novel. The theory used in this research is patriarchal theory by Sylvia Wallby and oppression theory by Iris Marion Young; the methodology employed is qualitative research in which the researcher tried to present the issues descriptively. As for the data, they were collected from the text in the novel. The text in novel were taken out as primary data. The data validation technique uses triangulation of theory. The results of this research finds that the forms of violence at Taliban’s patriarchal system that occurs in private and public patriarchy are school prohibition, work prohibition and limited to public access. The form of violence women in the Taliban affect women powerlessness are injustice in developing capacity, lack of decision making, lack of power and exposure to ill-treatment.